Cold Aim - Cantore, Janice (Carol Stream, Illinois : Tyndale House Publishers, Inc., 2019)
"Police Chief Tess O'Rourke's small town is still reeling from a devastating fire when the FBI asks for help: Could she shelter a witness in a high-profile human trafficking case? Initially reluctant to put the townspeople of Rogue's Hollow at risk, Tess is swayed after she sees Pastor Oliver Macpherson's genuine conviction to rescue those in need, a trait in him she's coming to love more each day. Tess's fledgling faith is tested when crews of workmen from out of town come in to assist with the fire cleanup and she worries that one of these strangers might shine a light on things best kept hidden. Neither she nor Oliver knows that Rogue's Hollow is already home to a suspect from a twenty-five-year-old murder case ... and someone is taking cold aim at those Tess is sworn to protect."--
Keywords: Women police chiefs -- Fiction; Human trafficking victims -- Fiction; Murder -- Fiction -- Investigation; Man-woman relationships -- Fiction; Christian fiction; Religious fiction; Detective and mystery fiction